2021
DOI: 10.31234/osf.io/fs4x8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transdiagnostic Processes as Mediators of Change in an Internet-delivered Intervention based on the Unified Protocol

Abstract: Background: Transdiagnostic treatments target shared mechanisms between disorders to facilitate change across diagnoses. The Unified Protocol (UP) aims at changing dysfunctional reactions towards emotions by increasing mindful emotion awareness and cognitive flexibility, as well as decreasing anxiety sensitivity and emotion avoidance. Method: We investigated whether these transdiagnostic processes were malleable by treatment and mediated the relationship between treatment and outcome in an internet-delivered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…These findings could offer some significant points that might be used to prevent the development of psychopathology, especially major depression, and reduce symptom severity. In addition, since concepts such as emotion regulation and cognitive flexibility are described as transdiagnostic factors (e.g., Kring ve Sloan, 2009;Schaeuffele et al, 2022) related to different psychopathologies, it is recommended that this model be tested on different psychopathology symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These findings could offer some significant points that might be used to prevent the development of psychopathology, especially major depression, and reduce symptom severity. In addition, since concepts such as emotion regulation and cognitive flexibility are described as transdiagnostic factors (e.g., Kring ve Sloan, 2009;Schaeuffele et al, 2022) related to different psychopathologies, it is recommended that this model be tested on different psychopathology symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive flexibility and mindful emotion awareness have emerged as the leading "active ingredients" in UP treatment (Schaeuffele et al, 2021), with indirect (mediating) effects on symptom outcomes over and above reduced experiential avoidance or increased behavioral activation. Notably, one study has demonstrated that all modules of the UP lead to similar changes in anxiety, and there are no significant differences between modules in terms of prediction of mechanisms of change (including cognitive skills acquisition), though the mindful emotion awareness module has a specific effect on mindfulness (Southward et al, 2023).…”
mentioning
confidence: 99%
“…Another recent example showed that mindfulness is a robust mechanism of change of in a transdiagnostic treatment of patients with depression or anxiety (Schaeuffele et al, 2021).…”
Section: Er As a Mechanism Of Change In Internet Interventionsmentioning
confidence: 99%